Conversations about mental illness and health in adult audiological rehabilitation. (1st March 2023) - Laird, Emma C.; Bryant, Christina A.; Barr, Caitlin M.; Bennett, Rebecca J.
Abstract: Objective: To understand the nature of mental health discussions in audiological rehabilitation, specifically, the types of conversations, when and how they are initiated, and the participant factors associated with discussing mental health. Design: A cross-sectional descriptive survey including quantitative (multiple choice) and qualitative (free-text) questions regarding mental health discussions between audiologists and clients. Study sample: A convenience sample of 118 Australian audiologists working in adult audiological rehabilitation. Results: The majority of participants (95.8%) reported having engaged in discussions with clients about mental illness and health at some point throughout their career. The frequency of these discussions varied across participants: 7% rarely discuss, 50% discuss occasionally, 30% discuss with about half their clients and 13% have discussions with most clients. Many participants (85.6%) reported that clients would initiate these conversations, most often via disclosing the impacts of hearing loss on clients' lives. Conclusions: Most audiologists will encounter clients with mental health concerns, and many will engage in conversations about psychological symptoms, therefore, training audiologists to recognise and address verbal and non-verbal cues regarding mental health may help to promote person-centred care and potentially improve outcomes.